Mechanism and design of intermittent aeration activated sludge process for nitrogen removal - Hanhan, Oytun; Insel, Güçlü; Yagci, Nevin Ozgur; Artan, Nazik; Orhon, Derin (Informa UK Limited, 2011)
The paper provided a comprehensive evaluation of the mechanism and design of intermittent aeration activated sludge process for nitrogen removal. Based on the specific character of the process the total cycle time, (T(C)), the aerated fraction, (AF), and the cycle time ratio, (CTR) were defined as major design parameters, aside from the sludge age of the system. Their impact on system performance was evaluated by means of process simulation. A rational design procedure was developed on the basis of basic stochiometry and mass balance related to the oxidation and removal of nitrogen under aerobic and anoxic conditions, which enabled selected of operation parameters of optimum performance. The simulation results indicated that the total nitrogen level could be reduced to a minimum level by appropriate manipulation of the aerated fraction and cycle time ratio. They also showed that the effluent total nitrogen could be lowered to around 4.0 mgN/L by adjusting the dissolved oxygen set-point to 0.5 mg/L, a level which promotes simultaneous nitrification and denitrification.
Keywords: Sewage; Nitrogen; Denitrification; Aerobiosis